The novel surfactant protein SP-H enhances the phagocytosis efficiency of macrophage-like cell lines U937 and MH-S - Diler, Ebru; Schicht, Martin; Rabung, Andrea; Tschernig, Thomas; Meier, Carola; Rausch, Felix; Garreis, Fabian; Bräuer, Lars; Paulsen, Friedrich (BMC Research Notes, 2014)
Surfactant proteins (SP) secreted by alveolar type 2 cells, play an essential role in maintaining the air-liquid barrier of the lung and are also involved in the opsonisation and clearance of bacteria by phagocytes. We have recently described a novel surfactant protein, SP-H (SFTA3). Expression of SP-H was earlier demonstrated to be upregulated by LPS and negatively regulated by IL-1? and IL-23 in vitro. The influence of SP-H on phagocytosis was measured using a murine and a human phagocytic cell line and fluorescent latex beads.SP-H markedly increases phagocytosis in vitro in the murine-derived alveolar macrophage cell lines MH-S and in human-derived differentiated U937 cells.It can be assumed that SP-H is involved in regulating phagocytic activity of macrophages. SP-H is a new player in pulmonary host defence.
EVALuna2:4439